1992
DOI: 10.1021/np50086a003
|View full text |Cite
|
Sign up to set email alerts
|

A Bioassay for Inhibition of Serotonin Release from Bovine Platelets

Abstract: A bioassay was developed to study agents capable of inhibiting the release of serotonin from bovine blood platelets. It is a simple, inexpensive, and reproducible high-throughput bioassay suitable for quality control of feverfew, Tanacetum parthenium, a crude drug with proven migraine prophylactic activity that is being considered for governmental registration and regulation. The bioassay, which requires no experimental animals or human subjects, was used to assess the in vitro activity of T. parthenium sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 42 publications
1
33
0
2
Order By: Relevance
“…This was felt to be due to variation in content and lack of standardization in different preparations. Marles et al [69] found wide variation in the amount of the active ingredient, parthenolide, from a variety of samples from 10 different regions of Europe. Feverfew inhibits serotonin release from aggregating platelets [69,70], as well as possibly inhibiting cell phospholipases, which prohibit release of arachadonic acid as part of the inflammatory response [71].…”
Section: Review Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This was felt to be due to variation in content and lack of standardization in different preparations. Marles et al [69] found wide variation in the amount of the active ingredient, parthenolide, from a variety of samples from 10 different regions of Europe. Feverfew inhibits serotonin release from aggregating platelets [69,70], as well as possibly inhibiting cell phospholipases, which prohibit release of arachadonic acid as part of the inflammatory response [71].…”
Section: Review Of Researchmentioning
confidence: 99%
“…Marles et al [69] found wide variation in the amount of the active ingredient, parthenolide, from a variety of samples from 10 different regions of Europe. Feverfew inhibits serotonin release from aggregating platelets [69,70], as well as possibly inhibiting cell phospholipases, which prohibit release of arachadonic acid as part of the inflammatory response [71]. Although it has been found to reduce 86% to 88% of prostaglandin production, it is not found to inhibit cyclooxygenase [72].…”
Section: Review Of Researchmentioning
confidence: 99%
“…Sesquiterpene lactones containing an c~-methylene butyrolactone unit, including parthenolide isolated from Tanacetum parthenium, caused changes in AA metabolism, through a mechanism probably not involving phospholipase inactivation. These data suggest a possible interaction of these compounds with PKC [18,19].…”
Section: Discussionmentioning
confidence: 69%
“…After centrifugation the supernatant was subjected to scintillation counting. 31 Structure Representations. Single low-energy 3D conformations were generated by CORINA.…”
Section: Methodsmentioning
confidence: 99%